2015
DOI: 10.3233/jad-141506
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Drugs and Risk of Alzheimer's Disease: An Updated Systematic Review and Meta-Analysis

Abstract: Observational studies support the use of NSAIDs for prevention of AD, but RCT do not. Well-designed studies and innovative approaches are required to illuminate the exact relationship between NSAID use and AD risk. The appropriate dosage and duration of use to benefit and the safety are also needed to determine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(142 citation statements)
references
References 0 publications
3
136
2
1
Order By: Relevance
“…These proinflammatory molecules could participate in AD pathogenesis either directly, by affecting brain Aβ metabolism (via entry to the CNS through the BBB or neural afferent pathways such as the vagus nerve) 134,135 or indirectly, by affecting Aβ metabolism in the periphery. In this regard, the results of observational studies show that NSAID use is associated with a reduced risk of AD 136 . These findings suggest that chronic systemic inflammation promotes the AD process.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…These proinflammatory molecules could participate in AD pathogenesis either directly, by affecting brain Aβ metabolism (via entry to the CNS through the BBB or neural afferent pathways such as the vagus nerve) 134,135 or indirectly, by affecting Aβ metabolism in the periphery. In this regard, the results of observational studies show that NSAID use is associated with a reduced risk of AD 136 . These findings suggest that chronic systemic inflammation promotes the AD process.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs (NSAIDs ) are well known inhibitors of COX-1 and COX-2. Their involvement in AD has first been suggested by studies which evidenced a reduction of AD risk in patients treated by NSAIDS [24][25][26] . In the majority of organs and tissues, COX-1 is constitutively expressed and COX-2 gene expression is induced especially in case of inflammation.…”
Section: Neuroinflammation and Ad: Role Of Arachidonic Acid And Its Dmentioning
confidence: 98%
“…Despite the data of retrospective epidemiologic studies which reported a lower AD risk in NSAIDStreated populations, randomized controlled trial failed to support the efficiency of these drugs in the AD therapy 26,38 . Therefore, other approaches are needed to explain the discrepancy between the data of the observational studies or the works on AD animal models on one hand and those of the clinical trials on the other hand.…”
mentioning
confidence: 99%
“…Применение нестероидных противовоспалительных средств (НПВС), по данным нескольких метаанализов, ассоциируется со снижением частоты развития деменции [34,35]. Однако многоцентровые плацебо-контролируе-мые исследования не показали эффективности НПВС (при значительном увеличении числа нежелательных, преимущественно желудочно-кишечных осложнений), в частности напроксена (220 мг три раза в день) или целе-коксиба (200 мг два раза в сутки) [36].…”
Section: профилактика ба на основе лекарственных средствunclassified